A Three-Layer Conceptual Content Model for Life Safety Education in Engineering Programs (International Journal of Scientific Trends, 2026)
This paper presents a three-layer conceptual content model for life safety education in technical and engineering programs. The model addresses the critical gap between theoretical safety knowledge and professional competency development by integrating: (1) an invariant theoretical core providing universal safety principles, (2) profession-specific contextual modules adapting content to engineering disciplines, and (3) an integrative practical product chain requiring students to create authentic workplace artifacts. The framework transforms content delivery from knowledge transmission to competency demonstration through a structured hazard-risk-control-evidence chain. This model operationalizes the risk-based thinking approach in engineering education and ensures constructive alignment between content, pedagogy, and assessment through artifact-based evaluation.